Effectiveness of an educational video on concussion knowledge in minor league hockey players: a cluster randomised controlled trial. Issue 2 (5th August 2013) - Cusimano, Michael D; Chipman, Mary; Donnelly, Peter; Hutchison, Michael G
Abstract : Background: With the heightened awareness of concussions in all sports, the development and implementation of effective prevention strategies are necessary. Education has been advocated as an effective injury prevention intervention. Purpose: To examine the effectiveness of the 'Smart Hockey: More Safety, More Fun' video on knowledge transfer among minor league hockey players. Study Design: Cluster-randomised controlled trial. Methods: A total of 267 participants from two age divisions and competitive levels were assigned to either a video or no-video group. The video was shown (or not shown) to the entire team as a result of random assignment. To evaluate the effectiveness of the educational video, questionnaires specific to concussion knowledge and players' attitudes and behaviours were completed. Results: There was a significant increase in the players' concussion knowledge scores immediately following exposure to the video (F(1, 103)=27.00, p<0.001). However, concussion knowledge at 2 months was not significantly different between the video and no-video groups, after controlling for prior knowledge level, age and competitive level (F(1, 115)=0.41, p=0.523). Similarly, players' attitudes and behaviour scores at 2 months did not differ between groups (F(1, 115)=0.41, p=0.507). Conclusions: We were able to show that a single viewing of an educational video in hockey could immediately improve knowledge about concussion but that this effect was transient and lost at 2-month follow-up. Future prevention endeavours in hockey and other sports should attempt to incorporate strategies and modalities to enhance knowledge retention.